Noninvasive aortic imaging - Baliyan, Vinit; Verdini, Daniel; Meyersohn, Nandini M. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
Non-invasive imaging of the aorta has undergone considerable advancements in recent times; largely driven by the technological advances in computed tomography (CT) and magnetic resonance imaging (MRI). This review article highlights these recent advancements and discusses the current role of different imaging tools in the management of aortic diseases.